Near‐Infrared‐Responsive Rare Earth Nanoparticles for Optical Imaging and Wireless Phototherapy - Du, Pengye; Wei, Yi; Liang, Yuan; An, Ran; Liu, Shuyu; Lei, Pengpeng; Zhang, Hongjie (Advanced science, 2024)
Near‐infrared (NIR) light is well‐suited for the optical imaging and wireless phototherapy of malignant diseases because of its deep tissue penetration, low autofluorescence, weak tissue scattering, and non‐invasiveness. Rare earth nanoparticles (RENPs) are promising NIR‐responsive materials, owing to their excellent physical and chemical properties. The 4f electron subshell of lanthanides, the main group of rare earth elements, has rich energy‐level structures. This facilitates broad‐spectrum light‐to‐light conversion and the conversion of light to other forms of energy, such as thermal and chemical energies. In addition, the abundant loadable and modifiable sites on the surface offer favorable conditions for the functional expansion of RENPs. In this review, the authors systematically discuss the main processes and mechanisms underlying the response of RENPs to NIR light and summarize recent advances in their applications in optical imaging, photothermal therapy, photodynamic therapy, photoimmunotherapy, optogenetics, and light‐responsive drug release. Finally, the challenges and opportunities for the application of RENPs in optical imaging and wireless phototherapy under NIR activation are considered. In this review, the authors focus on rare earth nanoparticles (RENPs) as media for light conversion and discuss the photoconversion process under near‐infrared (NIR) excitation, as well as recent achievements in optical imaging, photothermal therapy, photodynamic therapy, photoimmunotherapy, optogenetics, and light‐responsive drug release. Finally, the opportunities and challenges of NIR‐responsive RENPs for optical imaging and wireless phototherapy are discussed.